Site Selection of Ecotourism Development - Frida Purwanti (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2010)
This paper discusses the application of Criterium Decision Plus program in decision making process for selection of ecotourism development area. The selection was build based on some variable collected from stakeholders which were constructed in hierarchy system and be evaluated by an expert to decide the potential location using pairwise comparison. The result showed that for ecotourism development, the significance factor is government policy; the importance actor is government; the importance goal is increasing income and priority location is coastal area. Keywords : Ecotourism, Decision Making